Burp! - MacDonald, Alan, 1958-; Roberts, David, 1970- (North Mankato, Minn. : Capstone Stone Arch Books, 2012)
Bertie is convinced that the grumpy school janitor is a vampire, but locking Mr. Grouch in a shed is probably not a good idea--and that is only the first trouble that Bertie finds in this trio of stories.
Originally published: London : Stripes, 2010.
Keywords: Janitors -- Juvenile fiction; Elementary schools -- Juvenile fiction; Janitors -- Fiction; Schools -- Fiction; Humorous stories